Development and evaluation of a simultaneous and efficient quantification strategy for final prostanoid metabolites in urine. (June 2020) - Zhang, Tian-qi; Kuroda, Hirotaka; Nagano, Kazuya; Terada, Soshi; Gao, Jian-Qing; Harada, Kazuo; Hirata, Kazumasa; Tsujino, Hirofumi; Higashisaka, Kazuma; Matsumoto, Hiroshi; Tsutsumi, Yasuo
Highlights: We developed a method that can simultaneously quantify the prostanoid metabolites from a urine volume of approximately 1 mL. We demonstrated that the method is suitable for understanding the alternation of PNs in blood from metabolites in urine. We validated the practicality of our method by determining the metabolite profiles in the urine of Crohn's disease patients. Abstract: Prostanoids (PNs) play critical roles in various physiological and pathological processes. Therefore, it is important to understand the alternation of PN expression profiles. However, a simultaneous and efficient quantification system for final PN metabolites in urine has not yet been established. Here, we developed and evaluated a novel method to quantify all final PN metabolites. By purification using a reverse phase solid phase extraction (SPE) column, the matrix effects against the final PGD2, PGE2, and PGF2α metabolites were low, and their accuracies were nearly 100%. The matrix effects against the final PGI2 and TXA2 metabolites were high using reverse phase SPE column purification alone. By applying a tandem SPE method that combined reverse phase and ion exchange SPE columns, the matrix effects decreased so that the accuracy was nearly 100%. To validate the reliability of the method, each final metabolite was quantified from mouse urine to which the PNs (PGD2, PGE2, and PGI2 ) were intravenously administered. As a result, the amounts of PN metabolites were correlated with those of the PNs administered to the blood in a dose-dependent manner. To validate the method using human samples, the urinary metabolites of Crohn's disease (CD, a PN-related disease) patients and healthy individuals were quantified. All five metabolites were successfully quantified. Only final PGE2 metabolite levels were significantly higher in CD patients than those in healthy individuals, so that the urinary metabolite profiles of CD patients is determined. In conclusion, we developed a novel method to quantify all final PN metabolites simultaneously and efficiently and demonstrated the practicality of the method using human CD patient samples.